Study on Temporal and Spatial Characteristics of Overlying Strata in the Deep Coal Mining Process - Bang’an Zhang; Yushun Yang; Dongming Zhang (Advances in Civil Engineering)
This study adopts the stress relief method to test the in situ stress in the field to obtain the in situ stress distribution characteristics of no. 2 + 3# coal seam. A three-dimensional model was established with the no. S3012 working face as the engineering background, and the measured in situ stress values were applied to the three-dimensional model, and the spatial-temporal evolution characteristics of coal and rock mass around the stope during coal seam mining were studied. The specific conclusions are as follows: the three-dimensional stress distribution map in front of, behind, and on both sides of the working face in the process of coal mining are obtained. As the working face goes on, the maximum value of the supporting stress formed in front of, behind, and on both sides of the working face shifts to the corner, presenting a “hump-like” distribution. The stress concentration coefficient of front, back, and both sides of stope increases linearly with the increase of the mining size. Under the same mining size, the stress concentration coefficient in front of stope is the smallest, and the stress concentration coefficient on both sides is the largest. The three-dimensional displacement field distribution nephogram of overlying strata in the process of coal mining is obtained. With the continuous advance of the working face, the roof strata of coal seam undergo the continuous dynamic subsidence process, and the roof subsidence increases continuously, showing the shape of “bowl” with sharp bottom. In the process of working face mining, the roof displacement of coal seam showed an “O” shape evolution characteristic. The three-dimensional distribution cloud map of the plastic zone of coal and rock mass in the process of the working face mining was obtained, and the failure volume of the plastic zone gradually increases with the continuous progress of the working face.